Searching for a link between the L-BMAA neurotoxin and amyotrophic lateral sclerosis: a study protocol of the French BMAALS programme. Issue 8 (1st September 2014) - Delzor, Aurélie; Couratier, Philippe; Boumédiène, Farid; Nicol, Marie; Druet-Cabanac, Michel; Paraf, François; Méjean, Annick; Ploux, Olivier; Leleu, Jean-Philippe; Brient, Luc; Lengronne, Marion; Pichon, Valérie; et al.
Abstract : Introduction: Amyotrophic lateral sclerosis (ALS) is the most common motor neurone disease. It occurs in two forms: (1) familial cases, for which several genes have been identified and (2) sporadic cases, for which various hypotheses have been formulated. Notably, the β-N-methylamino-L-alanine (L-BMAA) toxin has been postulated to be involved in the occurrence of sporadic ALS. The objective of the French BMAALS programme is to study the putative link between L-BMAA and ALS. Methods and analysis: The programme covers the period from 1 January 2003 to 31 December 2011. Using multiple sources of ascertainment, all the incident ALS cases diagnosed during this period in the area under study (10 counties spread over three French regions) were collected. First, the standardised incidence ratio will be calculated for each municipality under concern. Then, by applying spatial clustering techniques, overincidence and underincidence zones of ALS will be sought. A case–control study, in the subpopulation living in the identified areas, will gather information about patients' occupations, leisure activities and lifestyle habits in order to assess potential risk factors to which they are or have been exposed. Specimens of drinking water, food and biological material (brain tissue) will be examined to assess the presence of L-BMAA in the environment and tissues of ALS cases and controls. Ethics and dissemination: The study has been reviewed and approved by the French ethical committee of the CPP SOOM IV (Comité de Protection des Personnes Sud-Ouest & Outre-Mer IV). The results will be published in peer-reviewed journals and presented at national and international conferences.